The implamentation of guided listening as a tool to enhance listening skill among 7th year students of basic education, at unidad educativa Llauro Damerval Ayora Nº1 in Loja city, during the school year 2014-2015 - Poma Macas, Hugo Mauricio (2016)
The present research work was developed with the goal of implementing Guided listening to improve students‘ listening skill. For the development of this work, some methods such as scientific, descriptive, analytic- synthetic and statistic were used. In the same way, instruments like tests, questionnaires, and observation sheets were also implemented to 37 students. The results obtained after the application of guided listening, revealed that students improved considerably their English listening skills, especially into the parameters of listening for comprehension and specific details. In conclusion, the application of Guided listening tool was effective because it encouraged students to continue improving the English language in all listening aspects.